Aplicando a regra do quadrado da soma de dois termos, calcule
Anexos:
![](https://pt-static.z-dn.net/files/d81/f778d8e61461613edceef8080a3a8500.jpg)
Geraldo5:
é (t+1/2)^2 ?
Respostas
respondido por:
4
A rega nos diz que (a+b)^2=(a+b)*(a+b)=a^2+a*b+b*a+b^2=a^2+2ab+b^2
então (a+b)^2=a^2+2ab+b^2, nosso a=t e nosso b=1/2. Substituindo:
(t)^2+2*(t)*(1/2)+(1/2)^2
t^2+t+1/4
=D
então (a+b)^2=a^2+2ab+b^2, nosso a=t e nosso b=1/2. Substituindo:
(t)^2+2*(t)*(1/2)+(1/2)^2
t^2+t+1/4
=D
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás